No association between the progesterone receptor gene polymorphism (+331G/a) and the risk of breast cancer: an updated meta-analysis - Xing-ling Qi; Jun Yao; Yong Zhang (BMC, 2017)
Abstract Background Many published studies have estimated the association between the +331G/A (rs10895068) polymorphism in the progesterone receptor (PgR) gene and breast cancer risk. However, the results remain inconsistent and controversial. To address this inconsistency, we systematically interrogated the aforementioned association via a meta-analysis. Methods Through a literature search, we identified 13 case-control studies, including 12,453 cases and 14,056 case-free controls. The strengths of reported associations were evaluated using odds ratios (ORs) with 95% confidence intervals (95%CIs). Results An association was found between +331G/A polymorphism and +331G/A risk in the dominant model (p = 0.027). Via subgroup analysis, we found no association between +331G/A and breast cancer risk in Caucasians, Asians or mixed racial groups. Conclusions Through meta-analysis, we were able to gain insight into previously reported associations between +331G/A polymorphism and breast cancer risk. However, further studies are still needed to provide more evidence.